Understanding the role of financial literacy, entrepreneurial literacy, and digital economic literacy on entrepreneurial creativity and MSMEs success: a knowledge-based view perspective - Muhammad Hasan; Miftahul Jannah; Tuti Supatminingsih; Muhammad Ihsan Said Ahmad; Masnawaty Sangkala; Marhawati Najib; Elpisah (Cogent Business & Management, 2024)
Business literacy is intellectual capital, which includes financial literacy, entrepreneurial literacy, and digital economic literacy, and its role in entrepreneurial creativity and the success of MSMEs is an important aspect to study, especially from a knowledge-based perspective. This research aims to identify and explore the influence of financial literacy, entrepreneurial literacy, and digital economic literacy on the success of MSMEs, with entrepreneurial creativity as a moderator variable. This research uses quantitative methods. The data collection technique used in this research is a questionnaire. The sample in this study was 700 respondents and were selected using purposive sampling techniques. Data analysis using PLS-SEM through Smart PLS software version 4. This research provides a comprehensive exploration and understanding of the fact that financial literacy, entrepreneurial literacy, and digital economic literacy are intangible assets that have an impact on business success. This research succeeded in finding and confirming that financial literacy, entrepreneurial literacy, and digital economic literacy have a positive and significant effect on the success of MSMEs through entrepreneurial creativity. This finding emphasizes the development of new concepts and insights related to intellectual capital in MSMEs that include financial literacy, entrepreneurial literacy, and digital economic literacy as part of intellectual capital in the knowledge-based view perspective.
Keywords: 650; Financial literacy; entrepreneurial literacy; digital economic literacy; entrepreneurial creativity; knowledge-based view and MSME success